2009
DOI: 10.1590/s0100-69912009000100012
|View full text |Cite
|
Sign up to set email alerts
|

Estudo randômico da correção cirúrgica do prolapso uterino através de tela sintética de polipropileno tipo I comparando histerectomia versus preservação uterina

Abstract: Estudo randômico da correção cirúrgica do prolapso uterino Estudo randômico da correção cirúrgica do prolapso uterino Estudo randômico da correção cirúrgica do prolapso uterino Estudo randômico da correção cirúrgica do prolapso uterino Estudo randômico da correção cirúrgica do prolapso uterino através de tela sintética de polipropileno tipo I comparando através de tela sintética de polipropileno tipo I comparando através de tela sintética de polipropileno tipo I comparando através de tela sintética de poliprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
0
6
1
6
Order By: Relevance
“…In some studies, it was showed that after hysterectomy and pelvic reconstruction with a mesh, mesh erosion rates are as high as 20% (12). In our study, we did not perform a hysterectomy and any peritoneal incisions, and we did not observe any mesh erosions.…”
Section: Discussioncontrasting
confidence: 40%
“…In some studies, it was showed that after hysterectomy and pelvic reconstruction with a mesh, mesh erosion rates are as high as 20% (12). In our study, we did not perform a hysterectomy and any peritoneal incisions, and we did not observe any mesh erosions.…”
Section: Discussioncontrasting
confidence: 40%
“…Korbly goes further to show that 36% of women preferred uterus preservation even if it has less surgical efficacy 20 . Uterus preservation at the time of TVM placement is plausible as demonstrated by various studies with equal or non-inferior surgical outcomes compared to those in concomitant hysterectomy 10 12 . Cure rates range from 75% to 98%, with the advantages of longer vaginal length, shorter operation time, less blood loss and less post-operation pain, which are all in agreement with this current study.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies on concomitant hysterectomy during TVM insertion used earlier mesh products, namely Nasca 10 , Perigee, Apogee 11 , Elevated system 12 and Prolift 7 . These reports varied in sample sizes (31–142 patients), mesh used and followed up periods (8.9–54 months), but they shared similar findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the deterioration of blood supply in the upper third of the vagina caused by a hysterectomy, the rate of mesh erosions is high and in some cases makes a subsequent sacrocolpopexy necessary. Some authors found mesh erosion rates as high as 20% after a hysterectomy and a pelvic reconstruction with a mesh [ 3 ]. The overall rate of mesh erosion after sacrocolpopexy in Nygaard et al was 3.4% (in 70 out of 2178 cases) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%